BUDAYA MASYARAKAT DAYAK SIANG MENGGUNAKAN DAUN GELINGGANG DALAM MENGOBATI PENYAKIT KULIT - Afra Aldilawulandari Annika Bharata; Carmelia Puteri Hendarsyah; Faiza Conita Chairiya Harahap; Siti Komariah; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Cassia alata L. or what can be called Chinese ketapang/Lewinggang leaf is a traditional medicine that is familiar to the Dayak Siang community. This plant has also been trusted for years to treat diseases on human skin with its natural properties. Although Gelinggang leaves were initially reported as wild plants, they can now be said to be plants that have economic value and have natural properties that really work to treat skin diseases. By using the literature method, we looked for various accurate information and sources in accordance with the data and facts explained by a journal, article or book that provides knowledge about the properties of gelinggang leaves as a medicine for skin diseases. The results of research from one source say that fungal infections on the skin such as tinea versicolor and athlete's foot can be treated effectively by antifungal compounds found in gelinggang leaves. This compound plays an important role in inhibiting the growth and development of fungi that cause skin infections, and helps the healing process of skin affected by the infection.